MANAGEMENT OF CHRONIC GINGIVOSTOMATITIS SUSPECTED DUE TO EOSINOPHILIC GRANULOMA IN DOMESTIC CATS - Fauzan, Adithya; Dewi, Ida Ayu Dian Kusuma; Erawan, I Gusti Made Krisna (Buletin Veteriner Udayana, 2026)
Feline Chronic Gingivostomatitis (FCGS) is an immune-mediated inflammatory disease in cats, characterized by ulcerative and/or proliferative lesions of the oral mucosa, with a reported prevalence of 10.9%–26% in certain populations. Its etiology presumably involves an abnormal cellular immune response to persistent antigens. In some cases, eosinophilic infiltration suggests involvement of the Eosinophilic Granuloma Complex (EGC). This report describes the clinical management and therapeutic response of a cat with FCGS and suspected EGC lesions. A 5-year-old male domestic cat presented with a history of painful mastication beginning in August 2024 and reccured in October 2024; intraoral examination revealed gingival ulceration and proliferation, while Diff-Quik cytology confirmed infiltration by eosinophils, hypersegmented neutrophils, and macrophages. A 7-day inpatient regimen of commercial wet food to reduce masticatory trauma, systemic glucocorticoids (methylprednisolone p.o. 1 mg/kg with tapering), and daily topical triamcinolone resulted in rapid clinical improvement—marked by reduced pain, decreased gingival inflammation, and a significant drop in inflammatory cells on repeat cytology. The combination of dietary texture modification and glucocorticoid therapy proved effective in reducing short-term inflammation in FCGS with suspected EGC, although mucosal biopsy remains recommended to confirm definitive remission and guide long-term follow-up.